Effect of Timing of Tracheostomy in Clinical Outcome of Neurocritical Patients. Early Versus Late Tracheostomy: A Tertiary Hospital-Based Study - Pradhan, Roshan; kc, Bidur; Kumari Mishra, Seema; kc , Bijay; Subedi , Prabin (Birat Journal of Health Sciences, 2024)
Introduction: The management of neurocritical patients requires the maintenance of the airway. Most frequently the patients need prolonged intubation or tracheostomy. Neurosurgeons frequently disagree about whether an early or late tracheostomy is best for neurologic recovery.Objectives: To assess the effect of early versus late tracheostomy in the clinical outcome of neurocritical patients.Methodology: This is a hospital based prospective observational study of all case of neurocritical patients between 1st January 2023 to November 2023 managed in Intensive care unit (ICU) of Kathmandu Medical College Public Limited. All of the patients required mechanical ventilation and subsequently underwent tracheostomy. The patients were allocated into two groups, using sealed envelope containing code numbers, Early tracheostomy group and late tracheostomy group. According to the timing of tracheostomy, early tracheostomy was defines as those done within 7 days of endotracheal intubation and late were those done thereafter.Data were tabulated and evaluated statistically using IBM SPSS 20.0. Continuous variables were compared using Independent sample t-test and discrete variables were compared using Mann-Whitney U test, Wilcoxon test and Asymp. Sig. (2-tailed) test with a p-value of 0.05 or less was considered significant.Results: There were 54 patients over study period of which 28 (51.86%) underwent early and late 26 (48.14%) underwent late tracheostomy. There were significant differences between the groups regarding the organism isolated, (p=0.0027) and the outcome in GOSE score (p = 0.013). There were no significant differences between the groups regarding the complication in ICU and duration of hospital stay.Conclusion: Early tracheostomy reduced the organism isolation, the mortality and morbidity. However, early tracheostomy did not reduce the ICU related complication, duration of hospital stay.